Late Palaeozoic tectonic setting of the southern Alxa Block, NW China: constrained by age and composition of diabase. Issue 8 (11th June 2017) - Zhang, Yiping; Zhang, Jin; Chen, Xuanhua; Wang, Yannan; Zhao, Heng; Nie, Fengjun; Zhang, Beihang
ABSTRACT: The ages of diabase outcropping on the southern Alxa Block and in related tectonic setting are not well constrained, but are important for exploring the tectonic evolution of the southern Alxa Block. The ages of the zircons from the diabase intruding the Middle–Late Cambrian Xiangshan Group were measured using sensitive high-resolution ion microprobe II (SHRIMPII) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), and the weighted mean ages of 276.8 ± 7.9 Ma and 276.2 ± 9.7 Ma were obtained, respectively. The major elements in the diabase indicate that it may belong to the tholeiitic series. With specific features of the rare earth elements (REEs) and trace elements, potentially affected by the continental crust based on the observed strong positive Pb anomaly, the diabase was produced in an intra-plate extension environment. Similar diabase/basalts were also found along the southern margin of the Alxa Block. Combined with sedimentary, palaeo-current, mafic, and felsic rocks in the southern Alxa Block, a back-arc extension environment potentially occurred in the southern Alxa Block during the Early–Middle Permian that resulted from the convergence between the North China Block (NCB) and the Yangtze Block.